A Comparative Study to Evaluate Efficacy and Safety of Daily Dosing versus Alternate-Day Atorvastatin Therapy in Patients with Dyslipidemia - Allen J. Rodrigues; Syed S. Farookh; Laxminarayana Kamath; Raveendra K.R (Universitas Padjadjaran, Indonesia, 2021)
Dyslipidemia is a well-recognized risk factor for the development of diseases associated with atherosclerosis, including coronary artery disease and stroke. Statins are the first choice hypolipidemic drug which are the most effective and best tolerated agents for treating dyslipidemia. Atorvastatin confers an HMG-CoA reductase inhibition up to 20-30 hours which makes it even effective on the next day. The present study is randomized open labeled study done at Victoria Hospital - Bangalore to compare efficacy and safety of daily dosing versus alternate-day atorvastatin therapy in patients with dyslipidemia. A total of 86 patients with dyslipidemia were randomized into 2 groups. Group A received 10 mg of atorvastatin daily (DS) and group B received 10 mg of atorvastatin on alternate day (AS) for six weeks. Among the 86 patients included in the study, mean age of the participants in the AS group was 53.12 ± 10.32 whereas that in the DS group was 52.26 ± 11.13. LDL-C decreased by 25.3% versus 22.4% (CI 0.95, P = 0.35) on daily and alternate-day dosing, respectively. Also 12.5% versus 15% (CI 0.95, P= 0.83) improvement was seen with HDL-C. Both dosage regimens provided reductions in total cholesterol (20.7% versus 20.2%) and triglyceride (20.7% versus 21.2%). There was no statistically significant difference in reduction in lipid parameters between two groups. Adverse effects were found less occurred in alternate day therapy than daily therapy. Gastrointestinal disturbances and myalgia were most commonly reported in both groups. Hence this study concludes alternate-day atorvastatin is as effective as daily atorvastatin in dyslipidemia.